AL-LUGHAH AL-‘ARABIYYAH WA AL-MUSLIMŪN: ‘AWĀMIL INTISYĀRIHĀ WA RUSŪKHIHĀ WA ĀTSĀRIHĀ - Muḥammad Mājid (Universitas Islam Negeri Ar-Raniry, 2016)
Arabic has been one of the most widely used languages in human communication not only because of its aspects surpassing those of other languages, but due to the Divine honor as the language of Holy Koran as Allah said ,”We made it an Arabic Koran that perhaps you will understand (alzukhruf , 3) This honor has enhanced and elevated the Arabic language status among the Arabs , its native speakers after all and among non-Arab Muslims, who found Arabic flexibility and potency of expression that their languages lack in addition to the holiness of Arabic as the language of the Koran and the Sunnah of the Prophet who is sent as Messengers for human beings. Due to the distinguished status of Arabic and its values for non-Arab Muslims, I addressed in this study not only the factors enhancing the usage of Arabic language by non-Arab peoples who embraced Islam and establishing. this language in the civilizations of these peoples, but also the impact of the Arabic language on their languages besides their cultural production, supporting my findings with the testimonies of objective researchers who had incontrovertible impact on the Arab civilization itself.